Edukasi dan Literasi Penyusunan Bisnis Plan Dalam Bewirausaha Bagi Mahasiswa Universitas Muhammadiyah Pontianak Kampus Sintang - Romi Ferdian; Zainur Ihsan; Putri Handayani (Universitas Teuku Umar, 2025)
This activity is a form of community service (PKM) carried out at Muhammadiyah University of Pontianak, specifically in the Management Study Program in Sintang, which is located in West Kalimantan. The purpose of this community service activity is to enhance students’ understanding and skills in developing a business plan as a fundamental basis for systematically and purposefully starting and managing a business. The target participants of this activity are students of the University of Muhammadiyah Pontianak, Sintang Campus, who have an interest in entrepreneurship. The methods applied include lectures, interactive discussions, and hands-on practice in preparing business plans based on each participant’s business idea. The results of the activity indicate that participants experienced an improvement in entrepreneurial literacy, particularly in understanding the structure, function, and benefits of a business plan in the business world. Moreover, this training encouraged the development of entrepreneurial spirit and creativity among students in formulating realistic and applicable business ideas. This activity is expected to serve as a sustainable initial step in shaping independent, innovative, and highly competitive students in the field of creative economy